A COMPARISON OF PARAMETER ESTIMATION OF LOGISTIC REGRESSION MODEL BY MAXIMUM LIKELIHOOD, RIDGE REGRESSION, MARKOV CHAIN MONTE CARLO METHODS - Autcha Araveeporn (My University, 2018)
The goal of this research is to estimate the parameter of logistic regression model.The coefficient parameter is evaluated by maximum likelihood, ridge regression, markov chain monte carlo methods.The logistic regression is considered the correlation between binary dependent variable and 2, 3, and 4 independent variables which is generated from normal distribution, contaminated normal distribution, and t distribution.The maximum likelihood estimator is estimated by differential the log likelihood function with respect to the coefficients.Ridge regression is to choose the unknown ridge parameter by cross-validation, so ridge estimator is evaluated on a form of maximum likelihood method by adding ridge parameter.The markov chain monte carlo estimator can approximate from Gibbs sampling algorithm by the posterior distribution based on a probability distribution and prior probability distribution.The performance of these method is compare by percentage of predicted accuracy value.The results are found that ridge regression are satisfied when the independent variables are simulated from normal distribution, and the maximum likelihood outperforms on the other distributions.
Keywords: Advanced Statistical Methods and Models